2018
DOI: 10.1590/s0102-053620180122
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock performance for cherry tomato production under organic, greenhouse production system

Abstract: Studies have indicated that grafting increases yield and prevents plant diseases. An experiment was installed to evaluate the influence of rootstock on the physicochemical and phytotechnical characteristics of a cherry tomato cultivar (Sweet Grape) under organic, greenhouse production system, from July to December 2014. The experiment consisted of a randomized complete block design, with eight replications. Treatments were composed of four rootstocks (Emperador, Muralha, Enforce, and Enpower) and the ungrafted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Mauro et al 14 . reported that grafting with rootstocks with different genetic backgrounds resulted in similar tomato fruit firmness among all rootstock treatments in a greenhouse study, which was also reported by Albino et al ., 9 who grafted cherry tomato with interspecific rootstocks ( S. lycopersicum × S. habrochaites ). However, in another study conducted in a plastic greenhouse, Romano and Paratore 37 found that fruit firmness of cherry tomato varied with rootstocks.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Mauro et al 14 . reported that grafting with rootstocks with different genetic backgrounds resulted in similar tomato fruit firmness among all rootstock treatments in a greenhouse study, which was also reported by Albino et al ., 9 who grafted cherry tomato with interspecific rootstocks ( S. lycopersicum × S. habrochaites ). However, in another study conducted in a plastic greenhouse, Romano and Paratore 37 found that fruit firmness of cherry tomato varied with rootstocks.…”
Section: Discussionsupporting
confidence: 64%
“…It has also been reported that rootstock effects on cherry tomato fruit total sugars, SSC, and TA were rootstock cultivar dependent 12,37 . However, Albino et al 9 . demonstrated that grafting cherry tomato with interspecific rootstocks ( S. lycopersicum × S. habrochaites ) resulted in similar SSC, TA, SSC/TA, and pH as the non‐grafted cherry tomato.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the best performance in this variable was observed with a high FPM content. On the other hand, it has been established that plants with a high number of leaves usually present a high yield, thus, leaves quantity was also measured during the experiments [78]. At 20 DAT, the plants with a high number of leaves were in the following order T 6 (31.50 ± 0.71) > T 8 (25.50 ± 4.92) > T 15 ∼ = C 1 (24.5 ± 0.70) > T 11 (24.0 ± 0.00) ∼ = T 9 (22.0 ± 2.83) > T 14 (21.67 ± 1.52) > T 12 ∼ = T 1 ∼ = T 4 (21.00 ± 2.0) whereas samples with a low number of leaves were T 3 (16.67 ± 5.51) < T 5 ∼ = T 7 (16.00 ± 0.0) < T 13 (15.50 ± 4.94).…”
Section: Characterization Of Soilless Substrates and Phenological Development Of Tomato In Different Substratesmentioning
confidence: 99%
“…Although countless researches have been done with regard to the quantitative and qualitative improvement of the tomato yield, there still remain undefined the technological measures, which ensure consumer safety and sustainability of the producer. The data from the scientific literature highlights the fact that in organic tomato crops, the number of fruits per plant, plant weight and yield are 30-70% lower than in conventional farming (Bilalis et al, 2018;Albino et al, 2018).…”
Section: Tomatoesmentioning
confidence: 99%